Administrative Mobbing in University Educational Environment: Methods of Elimination - KUZOVLEV, Valeriy Petrovich; PACHINA, Natalia Nikolaevna; KUZOVLEVA, Natalia Valeriyevna (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article reveals the essence of the ‘mobbing’ phenomenon, its kinds, classification attributes and reasons for the origin, development phases and the forms of mobbing realization. It describes the peculiarities of higher education organizational environment contributing to the mobbing development. Based on the specific features of university education functioning, it offers methods for administrative mobbing elimination and opposition.